“Evaluación de 4 moléculas de herbicidas en el cultivo de arroz (Oryza sativa l), en el Recinto Beldaco del Cantón Ventanas - Provincia de los Ríos” - Cepeda Zapata, Yandri Elián (2023)
The main difficulties that Ecuadorian rice producers have is the presence of weed species such as: blue straw (Echinocloas sp), false treadmill (Ischaemun rugosum), Indian beard (Fimbristilis), and dicotyledonous complexes of aquatic habit, all these weeds are economically detrimental to crops and in most cases the controls are deficient and cause resistance to herbicides. The present investigation was carried out in the rainy season in the year 2023 on the "4 hermanos" farm, owned by Mr. Arcadio Fortunato Cepeda Barco, in the Beldaco campus, Cantón Ventanas, Los Ríos Province, with the following UTM coordinates latitude: 1,373017 longitude: 79,530608. 5 treatments were established, being 4 chemical (post-emergent herbicides) cyhalofop butyl, pyrazosulfuron ethyl, metsulfuron methyl, Byspiribac sodium and an absolute control, in which the completely randomized block design (BCA) was used, with four repetitions with a planting frame of 0.40 cm row and 0.30 cm between plants. The variables were evaluated: toxicity index (7 and 14 days), weed control (21 and 28 days), plant height (7 and 14 days) and number of tillers (21 days). The lowest value of the toxicity index at 7 and 14 days occurred with the application of the herbicide Metsulfuron methyl at a dose of 18g/ha (1,00) and manual control (1,00). Among the results obtained, it was determined that the application at 21 days of Metsulfuron methyl at a dose of 18g/ha allowed to obtain good weed control (60%), as well as excellent weed control at 28 days (80%). The lowest value of the toxicity index at 7 and 14 days occurred with the application of the herbicide Metsulfuron methyl at a dose of 18g/ha (1,00) and manual control (1,00).